Knock phenomenon analysis on a diesel-CNG dual fuel engine using experimental fuel ratio - Ismail, Muammar Mukhsin (2021)
Knock avoidance is crucial to establish a proper Diesel-CNG Dual Fuel (DDF) engine. The causes of this phenomenon are still vague due to the lack of knock detection and characterization methods available. This study presents a knock characterization technique using a statistical analysis based on engine block vibration signal. Several experiments were conducted on a 2.5-litre converted DDF engine running at a constant engine speed between 1400 rpm and 3000 rpm with several diesel to CNG fuel ratio. This study found that when the diesel to CNG fuel ratio reached 70:30 at 1800 rpm to 3000 rpm, and 60:40 at 1400 rpm and 1600 rpm, engine knock was detected. A knock index was calculated from the vibration signal using Band-pass, Rectify, Integrate, and Compare (BRIC) method to determine knock intensity for each engine cycle. A three-sigma rule was applied to determine the threshold level of knock occurrence at the tested engine speeds. The knock thresholds at 1400 rpm, 1600 rpm, 1800 rpm, 2000 rpm, 2200 rpm, 2400 rpm, 2600 rpm, 2800 rpm, and 3000 rpm were found to have a knock index of 3.72, 3.49, 3.21, 2.71, 2.27, 1.80, 2.02, 1.80, and 1.73 respectively. Using a 5% knock cycle occurrence within the third and sixth standard deviation as a deciding criteria, a knock quality level was categorised as a vague, light, medium, and heavy knock. The analysed result shows that a severe knock occurred due to a sudden transition between a low and high knock intensity in a consecutive engine cycle, which yields a non-periodic mechanical shock. The calculated coefficient of variation of the knock index (COVKI) shows that the severe knock occurred when the COVKI is 0.30 and above. It suggests that the knock phenomenon on a DDF engine occurs due to an abrupt heat release rate during the mixing-controlled combustion phase and micro-explosion during the late combustion phase.